How do anti‐TNF therapies affect gait function in patients with rheumatoid arthritis?. (2nd July 2013) - Oda, Ryo; Fujiwara, Hiroyoshi; Tokunaga, Daisaku; Nakamura, Satoru; Taniguchi, Daigo; Kawahito, Yutaka; Seno, Takahiro; Matsui, Tomoyuki; Kubo, Toshikazu
Abstract Aim The aim of the present study was to investigate the influence of anti‐tumor necrosis factor (anti‐TNF) agents on gait function in patients with rheumatoid arthritis (RA). Methods Nine subjects with RA who were being treated with anti‐TNF agents, participated in this study. A motion capture system was utilized, and data from the force plate and captured three dimensional motions were analyzed.Gait evaluation was performed before and 5.8 ± 2.6 months after introducing the anti‐TNF agent. Stride, gait velocity and joint moments were calculated. In addition, an index of balancing weight of the lower extremities was determined. Results Stride length averaged 45.8 cm at baseline and 53.1 cm at the time of follow‐up, and gait velocity averaged 0.9 m/s at baseline and 1.1 m/s at the time of follow‐up. At heal contact, the joint moment of hip extension increased from 0.37 to 0.49, while ankle joint dorsiflexion moment increased from 0.08 to 0.13. During mid‐stance, knee joint extension moment decreased from 0.16 to 0.06. At toe‐off, hip joint flexion moment increased from 0.60 to 0.80, and ankle joint dorsiflexion moment increased from 0.80 to 1.05. The index of balancing weight of the lower extremities increased from 19.6 to 20.9 N. Conclusion The induction of anti‐TNF therapies improved alterations in shock absorption in the early stance phase, balancing weight of the lower extremities in mid‐stance, and increased push‐off power in the later stance phase.